The Top Ten Things a New Sci/Tech Librarian Should Know: Developing Core Competencies - Victoria S. Mitchell (Issues in Science and Technology Librarianship)
Summary of the STS Issues in Sci/Tech Library Management Discussion Group, ALA Annual Meeting, Toronto, June 22, 2003.